The role of surface functionalization of silica nanoparticles for bioimaging - Maria C. Gomes; Ângela Cunha; Tito Trindade; João P. C. Tomé (Journal of Innovative Optical Health Sciences, 2016)
Among the several types of inorganic nanoparticles available, silica nanoparticles (SNP) have earned their relevance in biological applications namely, as bioimaging agents. In fact, fluorescent SNP (FSNP) have been explored in this field as protective nanocarriers, overcoming some limitations presented by conventional organic dyes such as high photobleaching rates. A crucial aspect on the use of fluorescent SNP relates to their surface properties, since it determines the extent of interaction between nanoparticles and biological systems, namely in terms of colloidal stability in water, cellular recognition and internalization, tracking, biodistribution and specificity, among others. Therefore, it is imperative to understand the mechanisms underlying the interaction between biosystems and the SNP surfaces, making surface functionalization a relevant step in order to take full advantage of particle properties. The versatility of the surface chemistry on silica platforms, together with the intrinsic hydrophilicity and biocompatibility, make these systems suitable for bioimaging applications, such as those mentioned in this review.